1994
DOI: 10.1111/j.1528-1157.1994.tb01785.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Seizure Frequency 1 Week and 6, 12, and 24 Months After Surgery of Epilepsy

Abstract: We made quantitative analysis of seizure frequency 1 week and 6, 12, and 24 months after seizure surgery. Seizure recurrence was significantly higher when seizures occurred in the first postoperative week. Seizure recurrence increased progressively with longer follow-ups, but the 6 month postoperative follow-up period was an excellent index of long-term outcome. In operative follow-up studies, seizure frequency should be reported at fixed follow-up periods, e.g., at 6 months and 1, 2, 5, and 10 years. Meaningf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
5

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 15 publications
(14 reference statements)
5
33
0
5
Order By: Relevance
“…Maybe the worse longterm outcome originated from the preoperative long time course of seizures, which is thought to be important in the establishment of independent seizure foci (2). Another reason for the progressive deterioration could be the incomplete resection of the epileptogenic lesion, which led to progressive relapse of seizures (23,33). Nevertheless, the important message of the first study of Baumann et al (5) was the improvement of the seizure outcome after the complete removal of cavernoma-surrounding hemosiderin-stained tissue in patients with pharmacotherapy-refractory epilepsy.…”
Section: Outcome Versus Excision Of Surrounding Gliosismentioning
confidence: 97%
“…Maybe the worse longterm outcome originated from the preoperative long time course of seizures, which is thought to be important in the establishment of independent seizure foci (2). Another reason for the progressive deterioration could be the incomplete resection of the epileptogenic lesion, which led to progressive relapse of seizures (23,33). Nevertheless, the important message of the first study of Baumann et al (5) was the improvement of the seizure outcome after the complete removal of cavernoma-surrounding hemosiderin-stained tissue in patients with pharmacotherapy-refractory epilepsy.…”
Section: Outcome Versus Excision Of Surrounding Gliosismentioning
confidence: 97%
“…16,40,43 Illustrative Case This 3.5-year-old boy with TSC presented with a history of ~ 300 simple partial seizures per month, each described as a characteristic "stare" and clonic movements beginning in the left arm and progressing to the left leg and occasionally the right side. Multiple medications failed to treat the patient's condition.…”
Section: Neurosurg Focus / Volume 25 / September 2008mentioning
confidence: 99%
“…A patient with lateralizing ictal and interictal (i.e., concordant) EEG findings was classified as an optimal surgery candidate, whereas the patient with a nonlateralizing or contralatera1 ictal or interictal finding (i.e., discordant) was classified as a suboptimal candidate. Previous studies have suggested that these two groups may have differing base rates of surgery outcome (1 [8][9][10][11][12][13][14][15][16][17][18][19][20]. We recognize that this distinction is crude, and use it only to illustrate the interaction between base rate and predictive utility.…”
Section: Discussionmentioning
confidence: 99%
“…Auras were not considered seizures for the purpose of the study. A 6-month postoperative assessment of seizure status has been shown to be a good predictor of future seizure status (16). Of the 79 patients with LATL, 59 (74.7%) were seizure-free postopera- …”
Section: Methodsmentioning
confidence: 99%